The Influence of The Work Environment and Company Image on Employee Performance with Work Motivation as a Moderator at The Nizam Zachman Samudera Fishing Port Jakarta - Diansyah; Admiral, Muhammad Indra (Fakultas Ekonomi, Universitas Negeri Jakarta, Indonesia, 2024)
This study aims to examine the impact of work motivation moderation on employee performance at the Samudera Nizam Zachman Fisheries Port Jakarta by analyzing the influence of the work environment and company image. The study population consisted of 110 employees Data was collected and analyzed using SmartPLS to test the hypothesis. The results of the study show that the work environment has a positive and significant influence on employee performance, while the company's image does not show a significant relationship with employee performance. Work motivation is proven to have a positive and significant influence on employee performance, Motivation is able to moderate the influence of the work environment and company image on employee performance. This study has limitations on the independent variables studied, and recommends that the management of the Samudera Nizam Zachman Jakarta Fisheries Port pay attention to the work environment in employee placement to improve employee performance.